On a new class of Boolean dependencies - Huy, Nguyen Xuan; Thanh, Le Thi (Journal of Computer Science and Cybernetics, 2016)
A class of  generalized positive Boolean dependences (GPBD) is introduced. The membership problem, update problem and Armstrong relations for a given set of GPBD are investigated.